Teddy bear,teddy bear, count to ten - Krutop, Lee (Brimax Publishing Victoria, Australia, 2007)
This classic children's rhyme, presented in a captivating format, encourages early literacy and numeracy skills. The repetitive rhythm and simple storyline make it a perfect choice for bedtime reading or shared reading experiences.